An unusual thionyl chloride-promoted C−C bond formation to obtain 4,4'-bipyrazolones - Eller, Gernot A.; Vilkauskaitė, Gytė; Šačkus, Algirdas; Martynaitis, Vytas; Mamuye, Ashenafi Damtew; Pace, Vittorio; Holzer, Wolfgang (Beilstein Journal of Organic Chemistry, 2018)
Dialkyl 5,5'-dioxo-4,4'-bipyrazole-4,4'-dicarboxylates are readily obtained by the reaction of 5-hydroxypyrazole-4-carboxylates in refluxing thionyl chloride. The obtained diesters can be transformed into the corresponding 4,4'-bipyrazoles via alkaline hydrolysis and subsequent decarboxylation. Detailed NMR spectroscopic investigations (1H, 13C, 15N) were undertaken with all products prepared. Moreover, the structure of a representative 5,5'-dioxo-4,4'-bipyrazole-4,4'-dicarboxylate was confirmed by X-ray crystal structure analysis.
Keywords: dimerization; NMR (1H; 13C; 15N); pyrazolones; thionyl chloride; X-ray structure analysis